BS ISO 11617. Building and civil engineering sealants. Determination of changes in cohesion and appearance of elastic weatherproofing sealants after exposure of statically cured specimens to artificial weathering and mechanical cycling. (11th August 2021) - British Standards Institution,
No abstract available